Exportation to China and economy growth in Malaysia - Teo, Hui Hua (Universiti Malaysia Sarawak (UNIMAS), 2006)
This study is conducted to examine the relationship between exports growth and economic growth in Malaysia by emphasized China as the export destination using the historical data from 1990Q1 to 2003Q4. This study applied variety of analytical tools including Augmented - Dickey Fuller (ADF) unit root test, Johansen and Juselius cointegration test and Granger causality test to investigate the bi-directional relationship in short run and equilibrium relationship in long run between two variables. The finding revealed that exports growth to China and economic growth in Malaysia are integrated of order one and there exists a single cointegrating vector in the model under unit root test and cointegrating test respectively. Furthermore, the results suggest a bi - directional relationship in short run among exports growth to China and economic growth in Malaysia using Granger causality test. This study implies economic growth in Malaysia led exports growth to China hypothesis is valid in both the short run and long run.